Analysis On High School Students’ Mathematical Creative Thinking Skills on The Topic Of Sets - Sri Islami Kulsum; Tommy Tanu Wijaya; Wahyu Hidayat; Jessica Kumala (Mathematics Education Study Program, 2019)
The purpose of this research is to find students’ mathematical creative thinking skills on solving mathematical problems by using several indicators. This study was conducted in 1st Pasundan High school in Cimahi. The data analysis that would be use is the quantitative and qualitative descriptive analysis. The subject of this research are the 10th grade 2nd science students with a total of 22 students. The result of this research that is obtained from the fluency and flexibility indicator is in the low category with a percentage score of 56.8%, with an average of 2.27. When using the originality and elaboration indicator, it was also in the low category with a percentage score of 20.4% and 38.6% and average score of 0.81 and 1.54 respectively.